(untitled) (Web of Technology: Multidimensional Research Journal, 2024)
In this article, improving the expertise of traffic accidents based on the study of the braking process of motor vehicles Methodology and research methods are presented through theoretical studies based on the theory of car movement, experimental studies of the car braking process in different operating conditions, taking into account the structural characteristics of the car wheel.